2011
DOI: 10.1371/journal.pone.0018713
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of NF-κB Nuclear Translocation Is Regulated by PKA and A Kinase Interacting Protein 1

Abstract: The mechanism of PKAc-dependent NF-κB activation and subsequent translocation into the nucleus is not well defined. Previously, we showed that A kinase interacting protein 1 (AKIP1) was important for binding and retaining PKAc in the nucleus. Since then, other groups have demonstrated that AKIP1 binds the p65 subunit of NF-κB and regulates its transcriptional activity through the phosphorylation at Ser 276 by PKAc. However, little is known about the formation and activation of the PKAc/AKIP1/p65 complex and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 36 publications
4
49
0
Order By: Relevance
“…1E). We had identified AKIP1 as a PKA binding protein important in the retention and activity of PKA signaling (13,20), and PKA is thought to be essential in hypoxia and H/R (21). In ARVMs exposed to hypoxia and H/R, as expected, there was enhanced colocalization between AKIP1 and PKAc (Fig.…”
Section: Akip1supporting
confidence: 57%
See 1 more Smart Citation
“…1E). We had identified AKIP1 as a PKA binding protein important in the retention and activity of PKA signaling (13,20), and PKA is thought to be essential in hypoxia and H/R (21). In ARVMs exposed to hypoxia and H/R, as expected, there was enhanced colocalization between AKIP1 and PKAc (Fig.…”
Section: Akip1supporting
confidence: 57%
“…We believe that this protein has two distinct and crucial roles. The first role, as was previously published (16,20), is at the nucleus, where it interacts and enhances the role of PKA/NF-κB/SIRT1, and the second role is at the mitochondria. A key feature of cardiac protection is regulation of mitochondria under ischemic stress (41, 42).…”
Section: Discussionmentioning
confidence: 60%
“…It serves as a critical on/off switch for a number of key metabolic enzymes and is a regulator of gene transcription (40,41). For certain proteins (e.g., NF-κB), the function of PKA-mediated phosphorylation may be more akin to a rheostat (10,42). Along with other AGC kinases, PKA is also regulated by phosphorylation events.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it is well known that another ankyrin repeat protein, IB␣, masks the NF-B NLS sequence, thereby sequestering NF-B in the cytoplasm (37). Recently it was observed that this process is even more complex, since A kinaseinteracting protein 1 (AKIP1) and protein kinase A regulate the rate of NF-B translocation (15).…”
Section: Discussionmentioning
confidence: 99%